Environmental culture and local development. Challenges and perspectives (Review) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The formation of an environmental culture in the inhabitants of any country is essential to favor the care and conservation of environment and economic and social progress. Local development is one of the more wedged pointers due to degradation of the environmental conditions. The objective is to establish a relationship between the fromation process of the environmental culture on the students of the Municipal University Center in Niquero and the local development of the territory, its challenges and perspectives. Some ideas are included in this conservationist proposal, addressed to develop the efficiency in the process of formation of an environmental culture in the already mentioned students.
Keywords: environment, enviromental culture, local development, conservationist proposal